La comunicación como parte del desarrollo social para la prevención de la drogadicción en los adolescentes en el barrio Víctor Emilio Valdivieso (Tierras Coloradas) - Víctor Alfonso Reinoso Betancourt, Víctor Alfonso Reinoso Betancourt (2016)
This research work refers to " COMMUNICATION AS PART OF SOCIAL DEVELOPMENT FOR THE PREVENTION OF DRUG ADDICTION IN TEENS IN THE NEIGHBORHOOD Victor Emilio Valdivieso ( red earth ) " , which was determined as the central problem that drug addiction can be demonstrated in adolescents by the lack of information, education and family communication established as main objective to determine the impact that communication has to prevent drug abuse in teenagers in the neighborhood Victor Emilio Valdivieso ( Tierras Coloradas ) . For the development of this research work inductive, deductive, analytical, statistical methods and techniques of observation, surveys of the population of Tierras Coloradas , to interview the pastor , the district president and doctor were used , plus a procedure was performed systematic and analytical . Among the main results are that 58% of surveyed teens are male; 71% are aged between 16 a18 years, claiming a 51% of surveyed teens who talk with their parents about the issue of drug addiction; but they confirm that if you have any 45% go to their friends to consult them; 60% claim to not know about any case of drug addiction in the area; so the 33% of teens confirm that they have never used drugs; Re contradictions to respond the 54% who consume a drug like marijuana, making mostly for fun 37%; bringing consequences as; the low school performance by 45%; but making 91% if you have received information about drugs